La chapelle de l’ancien hôpital Saint-Lazare (Paris) - Agnès Chauvin (In Situ)
After 1794, the former convent of the Congregation of Saint Vincent de Paul, re-used as a prison for women, had become a sinister and badly maintained building which threatened ruin. The architect of the penitentiary administration demanded the urgent demolition of the convent’s old Gothic church. In 1823, a new chapel with an infirmary were built to the designs of Louis-Pierre Baltard (1764-1846), who had been appointed as architect for the prison administration of the Seine department ten years earlier. The chapel had a pseudo-basilical ground plan with a semi-circular apse, and had Doric columns. The building is characterised by its construction on two levels, with a sort of open basement level and generous side galleries. This design was intended to separate the entrances to keep the common law prisoners apart from the prostitutes and to prevent them from mingling in the nave. The church bears witness then to religious architecture during the period of the Restoration (1815-1830), a period which was not particularly prolific in its church building. It is also representative work for the architect Louis-Pierre Baltard who was an active participant in the architectural debates of his time but who in fact built very little. The former infirmary and the chapel were given statutory protection (inscription) on 28 November 2005.